1983
DOI: 10.1063/1.332437
|View full text |Cite
|
Sign up to set email alerts
|

Damage induced in Si by ion milling or reactive ion etching

Abstract: Surface damage in Si substrates created by Ar-ion milling or by reactive-ion etching in CF4, CHF3, Cl2, SiCl4, or SiF4 has been investigated. Metal-oxide-semiconductor capacitors were fabricated on the etched Si substrates, and the interface-state densities were obtained from capacitance-voltage measurements. Interface states generated by the dry etching processes were strongly dependent on the etching gas and the bias voltage. Carbon-based gases (CF4, CHF3) induced more interface states than those without car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(37 citation statements)
references
References 17 publications
3
34
0
Order By: Relevance
“…It has earlier been shown that the interface state density increases as the incident ion energy increases. 6 The high frequency C-V curve of our Ar etched sample shows a hysteresis effect, confirming that there is some degree of damage at the Si/Si02 interface during the etching. A negative flatband voltage shift of 2.5 V was also observed for the etched sample relative to the control.…”
Section: Resultssupporting
confidence: 74%
“…It has earlier been shown that the interface state density increases as the incident ion energy increases. 6 The high frequency C-V curve of our Ar etched sample shows a hysteresis effect, confirming that there is some degree of damage at the Si/Si02 interface during the etching. A negative flatband voltage shift of 2.5 V was also observed for the etched sample relative to the control.…”
Section: Resultssupporting
confidence: 74%
“…The high leakage current in the diodes with CF 4 /O 2 etched surfaces is attributed to the incomplete removal or reformation of oxide layer on the surface during RIE. Also, CF 4 based discharges are known to create higher degree of damage and surface roughness as observed in Si, 32,33 which may also explain the higher leakages observed in diodes with CF 4 /O 2 etched surfaces. The interfacial layer capacitance (C i = ε/δ) for the surfaces etched in CHF 3 /O 2 , CF 4 /O 2 , and CHF 3 / CF 4 were estimated to be 2.3, 1.5, and 25 µF/cm 2 , respectively.…”
Section: Reverse Characteristicsmentioning
confidence: 95%
“…RIE‐induced damage of the patterned area was therefore suspected. Shallow implantation of reactive ions as well as lattice damage has been shown to produce surface degradation in silicon . The right‐hand image in Figure C shows a PL image of a test wafer patterned using RIE, then doped using BBr 3 diffusion and finally passivated with ALD Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%